2008
DOI: 10.1111/j.1365-2486.2008.01717.x
|View full text |Cite
|
Sign up to set email alerts
|

Warming and drought alter C and N concentration, allocation and accumulation in a Mediterranean shrubland

Abstract: We investigated the effects of warming and drought on C and N concentrations, nitrogen use efficiency (NUE), and C and N accumulation in different ecosystem compartments. We conducted a 6-year (1999)(2000)(2001)(2002)(2003)(2004)(2005) field experiment to simulate the climate conditions projected by IPCC models for the coming decades in a Mediterranean shrubland. We studied the two dominant species, Globularia alypum and Erica multiflora, and an N-fixing species, Dorycnium pentaphyllum, also abundant in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 46 publications
(56 reference statements)
10
74
1
4
Order By: Relevance
“…In addition, the increase in the needle C:N ratio observed in P. purpurea in response to warming is a widely observed phenomenon in other tree species (Hobbie et al 2001;Olszyk et al 2003;Sardans et al 2008). The increases in the needle C:N ratio may influence plant-herbivore relationships because grazing pressure is correlated with foliar N concentrations (Sardans et al 2008). On the other hand, the increase in C:N ratio caused by LDET indicates relatively larger N-limitation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, the increase in the needle C:N ratio observed in P. purpurea in response to warming is a widely observed phenomenon in other tree species (Hobbie et al 2001;Olszyk et al 2003;Sardans et al 2008). The increases in the needle C:N ratio may influence plant-herbivore relationships because grazing pressure is correlated with foliar N concentrations (Sardans et al 2008). On the other hand, the increase in C:N ratio caused by LDET indicates relatively larger N-limitation.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, this increase of N allocation to woody tissue instead of leaves can affect the production capacity and seedling survival under long-term warming and competition conditions. In addition, the increase in the needle C:N ratio observed in P. purpurea in response to warming is a widely observed phenomenon in other tree species (Hobbie et al 2001;Olszyk et al 2003;Sardans et al 2008). The increases in the needle C:N ratio may influence plant-herbivore relationships because grazing pressure is correlated with foliar N concentrations (Sardans et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…The nutrient content of aboveground biomass, mainly in leaves, tends to decrease with drought (Sardans et al 2008a;b), with the exception of K that increases in some aboveground tissues of some plant species (Sardans and Peñuelas 2007a;Sardans et al 2008g). Drought increases the C:N and C:P ratios of Mediterranean shrubs and trees, associated with a protective and conservative mechanism (Inclan et al 2005;Sardans et al 2008b, c, d;Matías et al 2011) and with sclerophylly and increases in lignin content (Bussotti et al 2000;Sardans et al 2006a).…”
Section: Droughtmentioning
confidence: 99%
“…Most studies show that decreases in soil moisture also reduce N and/or P uptake by plants (Jupp and Newman, 1987;Sardans and Peñuelas, 2007;Cramer et al, 2009;Waraich et al, 2011), suggesting a negative feedback of less water and fewer nutrients on the production capacity and fitness of plants when drought persists or becomes more severe. As a result, plants under drought tend to produce leaves and litter with high C-nutrient ratios (Yarie and Vancleve, 1996;Sardans et al, 2008b;Limousin et al, 2010). The few studies of the specific effects of drought on the N-P ratio in plants, however, have not provided a clear conclusion (Sardans and Peñuelas, 2008;Sardans et al, 2008c, in spite of studies in gradients of water availability in Mediterranean regions that have observed a negative correlation between water supply and leaf N-P ratio (Sardans et al, 2011), an effect linked to higher growth capacity in plants with lower N-P ratios .…”
Section: Drought Shifts In Elemental Compositionmentioning
confidence: 99%
“…Plants respond by activating mechanisms for water conservation, which can frequently increase C-nutrient ratios in photosynthetic tissues (Sardans et al, 2008b(Sardans et al, , 2008c.…”
Section: Warmingmentioning
confidence: 99%